Sublethal and transgenerational effects of triflumezopyrim on the biological traits of the brown planthopper, Nilaparvata lugens (Stål) (Hemiptera: Delphacidae). (March 2019) - Xu, Pengfei; Shu, Runhang; Gong, Peipan; Li, Wenhao; Wan, Hu; Li, Jianhong
Abstract: Triflumezopyrim, a newly commercialized active ingredient developed by DuPont, has been defined as a novel insecticide in the mesoionic class. This insecticide has excellent bioactivity for sucking pests, such as the brown planthopper ( Nilaparvata lugens ), and was registered in China in 2016 for its control. However, the effects of triflumezopyrim on the growth and fecundity of brown planthopper have not yet been well studied. In this study, an age-stage life table procedure was used to evaluate the sublethal concentration (LC30 ) effects of triflumezopyrim on the biological parameters of N. lugens . Data from progeny (F1 generation) showed that the longevity, fecundity and egg hatchability of the F0 and F1 generations were not significantly affected by the LC30 of triflumezopyrim, although the developmental stages (except for the third stage), the adult preoviposition period (APOP), the total preoviposition period (TPOP) and the average duration of life ( T ) were significantly prolonged. Moreover, significant differences were not observed in the survival rates of different stages, the intrinsic rate of increase ( ri ), the finite rate of increase (λ) and the net reproductive rate ( R0 ). These results could provide a reference for further studies on the suitability and resistance mechanisms of the brown planthopper subject to a lethal dose of triflumezopyrim and reveal that triflumezopyrim could represent a candidate for N. lugens pest management in the next few years. Graphical abstract: Image 1 Highlights: The sublethal effects of triflumezopyrim on N. lugens were assessed. Adult longevity and fecundity of N. lugens were unaffected by triflumezopyrim. Triflumezopyrim increased the development rate of nymph stages of N. lugens.